Phosphorus Utilization Efficiency Among Corn Era Hybrids Released over Seventy-Five Years - Kwame Ampong; Chad J. Penn; James Camberato; Daniel Quinn; Mark Williams (Agronomy)
The high demands of corn (Zea mays L.) grain production coupled with water quality goals and phosphorus (P) conservation pose a great challenge to farmers and society and necessitate improved P utilization efficiency (PUtE: grain yield per mass total P (TP) content). The objective of this study was to evaluate PUtE among six Pioneer corn hybrids released over a span of 75 years. Corn was grown in a sand culture hydroponics system that eliminated confounding plant–soil interactions and root architecture and allowed for precise control of nutrient availability. Four P concentration levels (4, 7, 10, and 12 mg P L−1) were applied to hybrids released in 1936, 1942, 1946, 1952, 2008, and 2011. Nutrients other than P were applied at sufficient levels. Shoots and roots were harvested at maturity (R6) and biomass and P concentration determined. Results showed that total biomass did not differ among hybrids, but partitioning of biomass varied with hybrid. Grain yield varied between hybrids, but there was no trend with the year of release. Grain P content was negatively correlated with stem P content (R2 = 0.89). PUtE differed between the most recently released hybrids (2008 and 2011) whereas older hybrids had intermediate and similar PUtE. Grain yield was not solely determined by TP in the plant, but was strongly influenced by biomass and P partitioning, which was manifested as relative differences in PUtE between hybrids. While the PUtE did not necessarily change as a function of the breeding period, there were differences between hybrids. The findings highlight the critical role of the source–sink relationship in determining PUtE and grain yield.